The Effect of Achievement Content Exposure and Social Comparison on Social Pressure Study - Andara Jihan Az Zahra; Devi Purnamasari (Jogjakarta Communication Conference (JCC), 2026)
Social media usage among Indonesia’s Generation Z evolved beyond information and entertainment, empowering users as content creators who frequently showcased academic, career, and lifestyle achievements. Repeated exposure to these success narratives shaped digital social success standards, potentially increasing social pressure through social comparison. This study investigated the influence of achievement content exposure intensity and social comparison tendencies on perceived social pressure among Generation Z. A quantitative survey collected data from 102 active Indonesian Generation Z social media users using Likert-scale questionnaires that measured exposure intensity, social comparison behaviors, and social pressure levels. The data were analyzed with Partial Least Squares-Structural Equation Modeling. Results showed that exposure intensity had no significant effect, while social comparison positively influenced social pressure. The model explained that more than 50% of social pressure variation among respondents. Findings highlighted individual comparison tendencies over exposure frequency, contributing to digital communication studies on Generation Z social media experiences.